Characteristics of Hypertension Patients at Loa Bakung Community Health Center - Noorhayaty Noorhayaty; Iriyani Iriyani; Akhmad Azmiardi; Irfansyah Baharuddin Pakki (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Hypertension is a non- communicable disease that is one of the main causes of premature death in the world. The World health Organization (WHO) estimates that in 2025 there will be an increase in hypertension cases by around 80%, in 2000 from 639 million cases to 1.5 billion cases. Hypertension is the third leading cause of death in Indonesia for all ages. In 2015, surveys showed that 1 in 4 women and 1 in 5 men suffer from hypertension. Less than 1 in 5 people have hypertension that is well controlled and more than 9 million deaths are related to hypertension Objective : This study aims to determine the characteristics of hypertensive patients in Loa Bakung Community Health Center. The characteristics referred to gender, age, BMI, hypertension degree, and sub district. Research Methods/ Implementation Methods : The method used is descriptive, with a total sampling technique of 251 people. Results : The study results showed that 80 (31.9%) were male patients with hypertension, while 171 (68.1%) were female. There were 146 adult patients aged 18-59 (58.2%), and 105 elderly patients (41.8%) aged over 60 years. There were 96 hypertensive patients with a normal BMI (38.2%), 98 overweight patients (39%), and 57 obese patients (22.7%). The number of patients with normal hypertension (after regular treatment) was 67 (26.7%), 53 pre-hypertension patients (21.1%), 94 grade I hypertension patients (37.5%), and 37 grade II hypertension patients (14.7%). Patients who live in Loa Bakung sub-district are 220 (87.6%), Loa Buah sub-district 21 (8.4%), other sub-districts 10 (4%). Conclusion/Lesson Learned : The conclusion is that based on gender, there are more female patients than male patients, more adult hypertension patients (aged 15-59 years) than elderly patients, and more overweight patients have a BMI than other nutritional statuses. The number of hypertension patients with grade 1 hypertension is higher. Most hypertension patients who seek treatment at the Loa Bakung Community Health Center live in the Loa Bakung sub-district.